Methods for developing students’ self-awareness and reflective abilities - Kudratova Dildor Hikmatovna (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study aims to identify and analyze effective psychological and pedagogical methods for developing students’ self-awareness and reflective abilities as essential components of personal and professional growth. It focuses on constructing a reflective learning model that integrates metacognitive, emotional, behavioral, and motivational dimensions within higher education. Methods: The research employed a mixed-method design combining theoretical, empirical, and experimental approaches. It was conducted in three stages: theoretical analysis, diagnostic-experimental implementation, and evaluative reflection. Data were collected using self-awareness and reflection scales, self-assessment questionnaires, reflective diaries, and interviews. Statistical tools, including t-tests and correlation analysis, were applied to measure the effectiveness of the interventions. Results: Findings showed significant improvement in the experimental group’s self-awareness (+26%), emotional regulation (+21%), reflective thinking (+28%), and self-assessment accuracy (+24%) compared to the control group (p < 0.05). Students reported greater motivation, autonomy, and empathy, supported by enhanced metacognitive awareness and emotional intelligence. Conclusion: Systematic reflection-based pedagogy fosters deeper learning, self-regulation, and professional maturity. The integration of reflective dialogue, journaling, and portfolio-based learning effectively enhances students’ introspection, self-control, and adaptive capacity. Limitation: The study was limited to one academic institution and a 12-week intervention period, suggesting the need for longitudinal and cross-cultural research. Contribution: The research contributes a validated psychological-pedagogical model of reflective learning, offering practical strategies for embedding self-awareness development into higher education curricula to promote lifelong learning and self-directed growth.